Pengaruh Pemberian Serbuk Daun Sirsak terhadap Sitophilus oryzae pada Beras Selama Penyimpanan - Halifah Pagarra (Jurusan Biologi Universitas Negeri Makassar, 2008)
This study aims to determine the influence of leaf of Anona muricata L. powder against Sitophilus oryzae in rice during storage. This research is experimental research that uses experimental design with a basic design pattern randomize complete design. This study consists of four treatment groups (K0, K1, K2, and K3). K0 = control or no treatment; K1 = 10% (90 grams + 10 grams of rice powder leaves of Anona muricata L.); K2 = 20% (80 grams + 20 grams of rice powder leaves sirsak; K3 = 30% (70 grams + 30 grams of rice powder leaves Anona muricata L). Parameters measured the number of insects which declined during the 1 month storage. Data obtained in deskritif and analyzed statistically with inferensial test Fα = 0.05 followed by the LSD α = 0.05. Results of research indicate that the results of research show that the leaves of Anona muricata L powder. affect Sitophilus oryzae in rice during storage. Concentration of the most influential of Sitophilus oryzae in rice during storage is K3 (concentration 30%), the number of insects that are rejected 10 insects.